Gestational diabetes and acromegaly: Single‐centre experience of 14 pregnancies. (14th October 2019) - Vialon, Magaly; Grunenwald, Solange; Mouly, Céline; Vezzosi, Delphine; Bennet, Antoine; Gourdy, Pierre; Caron, Philippe J.
Abstract: Introduction: The prevalence of gestational diabetes (GD) in women with acromegaly is rarely reported. The aims of this study were to evaluate the prevalence of GD in acromegalic women submitted to a systematic screening for GD and then to compare women with or without GD. Patients and methods: We studied 14 pregnancies in 11 women (34.0 ± 3.6 years) treated with somatostatin analogues after a pituitary surgery (n = 6) or as primary (n = 5) therapy, and treatment was discontinued at the time of pregnancy diagnosis for 13 pregnancies. One woman was diagnosed with acromegaly during pregnancy and was treated with octreotide LAR between 12 and 18 weeks of gestation. Before pregnancy, no women had diabetes mellitus, and GH/IGF‐1 hypersecretion was uncontrolled in 6 women. Results: Gestational diabetes was diagnosed during 7 pregnancies (50%) in 6 women (one woman had GD during her 2 pregnancies), according to fasting blood glucose (n = 5) or to an oral glucose tolerance test (n = 2). Before pregnancy, IGF‐1 was not controlled in 4 GD+ and in 2 GD− women. Women with GD were not significantly older and had increased pregestational BMI ( P = .02), with a more frequent family history of type 2 diabetes, no personal history of GD but of macrosomia for one patient. Conclusion: The prevalence of GD in our women is higher than that reported in the literature, probably resulting from the systematic GD screening and to the age of women. Therefore, routine screening of GD should be considered in women with acromegaly, particularly in those with risk factors for GD and with uncontrolled IGF‐1 levels before pregnancy.